EPIDEMIOLOGIC AND ZOONOTIC RISK OF THE MALACOFAUNA FLUVIALAND TERRESTRIAL IN CAPITÁN ROBERTO FLEITES HEALTH AREA, CUBA - Fimia-Duarte, Rigoberto (2014)
The main objective was to identify the epidemiological and zoonotic risk of fluvial and terrestrial molluscs in the Health Area Roberto Fleites, municipality Santa Clara, Villa Clara province, Cuba. Snails were sampled monthly during 2011-2012. Mollusc species with greater frequency and distribution were Praticolella griseola, Tarebia granifera and Pseudosuccinea columella. The most medically important species were: P. griseola, Physella columella, Subulina octona, Physa acuta, Pomacea poeyana and Galba cubensis that are intermediate hosts and transmitters of parasitic helminth diseases. A greater abundance of molluscs in orchards organoponic in relation to bodies of water sampled was observed; however, higher species richness of molluscs was obtained in water bodies in the orchards-organoponics. There is an increased epidemiological risk-in organopónicos orchard, where 96.49% of molluscs are capable of transmitting disease to man and animals, while in the bodies of water, only 8.32% of the mollusks are capable of transmitting diseases to man and animals. Asignificant relationship between the mollusc and the maximum relative humidity and precipitation was evident.